Peran Implementasi Intelijen Bisnis Dalam Menentukan Peramalan Bisnis - Pratama, Afiq Arya; Pitoyo, Bayu Seno; Fauzi, Achmad; Rivaldi, Ahmad; Andini, Desvita Aisya (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2024)
This research aims to explore how the implementation of Business Intelligence (BI) impacts organizational performance. BI is a system used to gather, coordinate, and analyze information from various sources to support decision-making. The implementation of BI brings benefits to organizations, such as enhancing analytical capabilities and understanding business dynamics, as well as supporting better decision-making. This study investigates the subject with a subjective approach by analyzing various relevant references. The results show that BI execution has a positive impact on organizational performance by enhancing analytical capabilities, improving decision accuracy, and facilitating faster adaptation to market changes and business environments. Furthermore, the organization's role in decision-making is a key factor in the success of BI implementation. The findings of this research provide practical recommendations for organizations to effectively utilize BI to enhance competitiveness in the era of globalization. Keywords: Business Intelligence, Business Organization